The Influence of Exclusive Breastfeeding Toward The Occurrence of Childhood Pneumonia in East Java - Risa Ayu Wulandari (Jurnal Berkala Epidemiologi, 2018)
Background: East Java Province is the top three with the highest number of childhood pneumonia and the highest death from pneumonia in Indonesia. One of the factors that can prevent childhood pneumonia is to provide exclusive breastfeeding. Purpose: This study aimed to analyze the effect of giving exclusive breastfeeding on the incidence of childhood pneumonia in East Java Province in 2016. Methods: The design of this study used cross sectional method. This research is an observational analytic study using secondary data from the Health Profile of East Java Province publication in 2016. The population used is the East Java Province Health Profile data in 2012 to 2016, while the sample is the East Java Province Health Profile data in 2016. Data collection conducted in May 2018. The locations used in this study were 38 districts/ cities in East Java Province. Data analysis used a linear regression test with the dependent variable of childhood pneumonia cases and independent variables exclusive breastfeeding. Results: This study shows that there is an effect of exclusive breastfeeding on the incidence of childhood pneumonia with p value= 0.00 (p< 0.05). Exclusive breastfeeding has an effect of 34.70% on the incidence of childhood pneumonia with a strong moderate relationship. Conclusion: There is an influence between exclusive breastfeeding on the incidence of childhood pneumonia in East Java Province in 2016.